Spatial analysis of diarrhea in toddlers and environmental factors in the East Java Province Indonesia - Sakti, Eka Satriani; Makful, Martya Rahmaniati; Tampubolon, Romariana Dewi (BKM Public Health and Community Medicine, 2023)
Purpose: The objective of this study was to conduct spatial analysis on the incidence of diarrhea in toddlers in East Java and to examine its relationship with environmental factors such as percentage of families with access to proper sanitation (healthy latrines), percentage of ODF (Open Defecation Free) villages, and percentage of drinking water facilities that meet the requirements in each district/city in East Java. Methods: The study utilized a cross-sectional study design with the 2020 East Java Province Health Profile serving as the data source. Moran's Index and the LISA bivariate test were used for the spatial analysis. Results: The findings revealed that there is a spatial autocorrelation in the number of diarrhea cases in toddlers (I value: 0.28, p value: 0.009). Out of the districts/cities studied, only 5 exhibited significant spatial correlation (Gresik, Sidoarjo, Mojokerto, Magetan, and Surabaya City) based on the LISA bivariate test results. Conclusion: Efforts to decrease the incidence of diarrhea cases in toddlers should focus on increasing the scope of environmental health programs, particularly in quadrant 1 (High-High) and 2 (Low-High) areas. Further analysis is required within the sub-district and village scope.